Opinions of the urban women on pap test: evidence from Bangladesh - Mustari, Sohela; Hossain, Belal; Mohamad Diah, Nurazzura; Kar, Susmita (Asia Pacific Organization for Cancer Prevention (APOCP), 2019)
Each year, many countries from developed world publishes reports on early cancer detection; which is absolutely absent in most developing countries like Bangladesh.Very limited evidence is found on the role and acceptance of Pap test among the women of Bangladesh in determining cervical cancer. More research and updates are needed relating Pap test in early detection of cervical cancer. Thus the purpose of this study is set to assess the opinions of Bangladeshiurban womentowardsthe Pap test. A questionnaire-based survey of 400 Bangladeshi urban women was evaluated by on their socio-demographic characteristics, knowledgeand attitudes towards Pap testing. In general, the findings reveal that respondents havea good understanding of thepurpose of Pap test screening with 3.92 (Mean score). With 3.54 Mean score,the respondents believed that Pap tests are recommended to women who are married and with 3.45 mean score women believed that Pap tests arerecommended only to those who have children. Generally, respondents possess good knowledge of Pap test and its purpose. These findings can be used in identifying prospect cervical cancer screening significance populations and trend for future intrusion